KiSS1 in regulation of metastasis and response to antitumor drugs. (January 2019) - Corno, Cristina; Perego, Paola
Abstract: Metastatic dissemination of tumor cells represents a major obstacle towards cancer cure. Tumor cells with metastatic capacity are often resistant to chemotherapy. Experimental efforts revealed that the metastatic cascade is a complex process that involves multiple positive and negative regulators. In this respect, several metastasis suppressor genes have been described. Here, we review the role of the metastasis suppressor KiSS1 in regulation of metastasis and in response to antitumor agents. Physiologically, KiSS1 plays a key role in the activation of the hypothalamic-pituitary-gonadal axis regulating puberty and reproductive functions. KiSS1-derived peptides i.e., kisspeptins, signal through the G-protein coupled receptor GPR54. In cancer, KiSS1 signaling suppresses metastases and maintains dormancy of disseminated malignant cells, by interfering with cell migratory and invasive abilities. Besides, KiSS1 modulates glucose and lipid metabolism, by reprogramming energy production towards oxidative phosphorylation and β-oxidation. Loss or reduced expression of KiSS1, in part through promoter hypermethylation, is related to the development of metastases in various cancer types, with some conflicting reports. The poorly understood role of KiSS1 in response to chemotherapeutic agents appears to be linked to stimulation of the intrinsic apoptotic pathway and inhibition of cell defense factors (e.g., glutathione S-transferase-π) as well as autophagy modulation. Deciphering the molecular basis underlying regulation of the metastatic potential is crucial for the establishment of novel treatment strategies.